2022
DOI: 10.2196/37984
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Long COVID Symptom Patterns: Association Rule Mining and Sentiment Analysis in Social Media Tweets

Abstract: Background The COVID-19 pandemic is a substantial public health crisis that negatively affects human health and well-being. As a result of being infected with the coronavirus, patients can experience long-term health effects called long COVID syndrome. Multiple symptoms characterize this syndrome, and it is crucial to identify these symptoms as they may negatively impact patients’ day-to-day lives. Breathlessness, fatigue, and brain fog are the 3 most common continuing and debilitating symptoms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Callard and Peregov [48] reviewed how, through social platforms such as Twitter, patients made the persistence and heterogeneity of COVID-19 symptoms visible, thus catapulting the inclusion of post-COVID-19 condition as a relevant phenomenon in clinical and policy debates. In contrast, other authors in the last 2 years have explored on various platforms (including Twitter) the persistence of symptoms and emotional impact after months of suspected and confirmed diagnosis of COVID-19 [49][50][51][52][53][54][55], including the period of vaccination. Furthermore, others have explored web discussions regarding this phenomenon [56].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Callard and Peregov [48] reviewed how, through social platforms such as Twitter, patients made the persistence and heterogeneity of COVID-19 symptoms visible, thus catapulting the inclusion of post-COVID-19 condition as a relevant phenomenon in clinical and policy debates. In contrast, other authors in the last 2 years have explored on various platforms (including Twitter) the persistence of symptoms and emotional impact after months of suspected and confirmed diagnosis of COVID-19 [49][50][51][52][53][54][55], including the period of vaccination. Furthermore, others have explored web discussions regarding this phenomenon [56].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…In addition, the Stanford Dependency Parser (SDP) approach is utilized to extract implicit aspects, which consider the relationship between the opinion and aspects. Rule mining approaches are very much used in past literature for sentiment analysis [13,19,35]. The following sections go into detail about each of these components.…”
Section: Aspect Extraction and Associationmentioning
confidence: 99%
“…Their study showed fever, cough and malaise/body pain are the most common symptom. Matharaarachchi et al [52] used twitter data to discover symptom patterns. They extract tweets about COVID symptoms and by using ARM, identified frequent symptoms which were brain fog, fatigue, breathing/lung issues, heart issues, flu symptoms, depression, and general pains.…”
Section: Related Workmentioning
confidence: 99%